A Lightweight Design Method for Aviation Gear Web based on OptiStruct-Abaqus - Yandong Wang; Siyu Chen; Jinyuan Tang (Jixie chuandong)
Based on the structure optimization software OptiStruct and commercial finite element analysis software Abaqus, combined with the theory of topology optimization, dimension optimization and finite element contact analysis, an innovative lightweight design method of gear web structure is proposed to solve the problem of overweight of aeronautical gear. Taking the transmission gear of an aeroengine accessory as the research object, the web structure is designed by topology optimization and dimension optimization based on OptiStruct software. The contact performance of the gear is calculated by Abaqus software. The flow chart and key technology of lightweight design of the web structure are given. The actual optimal design results show that under the condition of guaranteeing strength and transmission error, the overall weight of the gear is reduced by 39.6%, and the effect of weight reduction is obvious, thus realizing the goal of gear lightweight design.